Trial of Agave Species in Lateriuc Areas of West Bengal - Banerjee, A. K. (Indian Forester, 1982)
Two species of Agave, namely, Agave sisalana (Keleghai of West Bengal and Sambalpur of Orissa provenances) and Agave cantala (Maharashtra provenance) were planted on an experimental scale in clearfelled areas under the high tension grids in laterite soils of West Bengal to determine their suitability. It was found that Agave cantala produces maximum dry fibre in the first three years among the tried varieties. Fertilizer and cleaning treatments indicated that none of the varieties can compete with Sal coppice crop. Further, 5.75 g of fertilizer of N : P : K (2 : 2 : 5) is better than the plots without any fertilization or with double the above dose. The additional fibre production due to application of the best fertilizer dose at an additional cost was found to be an economic proposition.